Engineering Students' Thinking About Technical Systems: An Ontological Categories Approach - Hofer, Sarah Isabelle; Reinhold, Frank; Loch, Frieder; Vogel-Heuser, Birgit (Frontiers in Education, 2020)
This paper aims at identifying ontological categories as higher-order knowledge structures that underlie engineering students’ thinking about technical systems. Derived from interviews, these ontological categories include, inter alia, a focus on the behavior, structure, or purpose of a technical system. We designed and administered a paper-based test to assess these ontological categories in a sample of N = 340 first-year students in different engineering disciplines. Based on their activation patterns across ontological categories, students clustered into six different ontological profiles. Study program, gender as well as objective and self-perceived cognitive abilities were associated with differences in jointly activated ontological categories. Additional idiosyncratic influences and experiences, however, seemed to play a more important role. Our results can inform university instruction and support successful co-operation in engineering.